Penerapan Inovasi Pelayanan Publik melalui Aplikasi E-TTSP pada Sistem Perizinan Terpadu Satu Pintu di Dinas Penanaman Modal Provinsi Banten - Dinar Handayani; Rashya Nabila Az Zahra; Khikmawanto Khikmawanto (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2026)
This study analyzes the implementation of public service innovation through the E-TTSP application at the Investment and One-Stop Integrated Services Agency (DPMPTSP) of Banten Province. Using a descriptive qualitative method, data were collected through interviews, observation, and document analysis. The results show that this digital system has significantly improved service quality and efficiency. Processing time was reduced from 7–14 days to only 2–5 days, while bureaucratic procedures were simplified. The system also enhances transparency, accountability, and accessibility, allowing users to apply online without visiting the office. Consequently, the investment climate improved, marked by a 28% increase in permit applications and a 35% rise in investment value within two years. However, challenges remain, including uneven network infrastructure, low digital literacy, and limited human resource capacity. It is recommended to improve infrastructure, provide continuous training, and intensify socialization. In conclusion, E-TTSP has delivered tangible benefits, yet sustainable development is necessary to ensure equal and optimal services for all.